Sustainable nation. Urban design patterns for the future. - Farr, Douglas (Wiley, 2018)
As a follow up to his widely acclaimed Sustainable Urbanism, this book from author Douglas Farr embraces the idea that the humanitarian, population, and climate crises are three facets of one interrelated human existential challenge, one with impossibly short deadlines. The vision of Sustainable Nation is to accelerate the pace of progress of human civilization to create an equitable and sustainable world. The core strategy of Sustainable Nation is the perfection of the design and governance of all neighborhoods to make them unique exemplars of community and sustainability. The tools to achieve this vision are more than 70 patterns for rebellious change written by industry leaders of thought and practice. Each pattern represents an aspirational, future-oriented ideal for a key aspect of a neighborhood. At once an urgent call to action and a guidebook for change, Sustainable Nation is an essential resource for urban designers, planners, and architects.
Keywords: Stadtentwicklung; Nachhaltige Entwicklung; Transformation; Stadtquartier; Öffentlicher Raum; Mobilität; Lokale Ökonomie; Gebaute Umwelt; Wohlbefinden